Digital applications inject new vitality into art education—path analysis based on data of art teachers in basic education in China - Shi, Jiawei (Frontiers in Education, 2025)
IntroductionThis study investigates the current state of art education in China from the perspectives of teacher resource allocation and educational funding. The analysis reveals significant challenges, including a low proportion of highly qualified teachers, imbalances in professional disciplines, and uneven geographical distribution of faculty. Furthermore, disparities in per-student funding, with some provinces falling below the national average, are attributed to uneven economic development and varying student populations in basic education. To bridge the “teacher resource gap” and promote educational equity, this research explores the potential of a comprehensive digital education model to enhance teaching quality and foster equality.MethodsA mixed-methods approach was employed, integrating literature review, policy analysis, and the interpretation of educational statistical reports. The study utilized surveys, the Delphi method, and the Analytic Hierarchy Process (AHP) to evaluate the current status and advantages of digitalization in basic art education. An evaluation framework based on the CIPP model was constructed, analyzing four dimensions: teaching resource allocation (X1), foundational teaching environment (X2), instructional process implementation (X3), and teaching effectiveness evaluation (X4). Expert authority was assessed, and an indicator weighting system was established.ResultsThe expert authority coefficient (Cr) was determined to be 0.632, indicating a high level of reliability. The weighted evaluation indicator system was formulated as Ȳ=0.35X1+0.15X2+0.22X3+0.28X4. The overall mean score for the surveyed subjects was Ȳ=2.726. A comparative analysis between traditional and digital schools showed that Digital Demonstration School A achieved Ȳ=2.721 (82.5 on a 100-point scale), while School B scored Ȳ=2.715 (78.25 on a 100-point scale).DiscussionThe results indicate that the implementation of digitalization has a demonstrably positive effect on the development and advancement of basic art education. The higher scores in digitally-equipped schools suggest that comprehensive digital models can effectively mitigate existing resource disparities and improve educational outcomes. Based on these findings and the current context of educational development, this study proposes a series of targeted and rational recommendations for policy-makers and educational institutions to further leverage digital technology in promoting equitable and high-quality art education in China.